In vitro metabolism of T-2 toxin in rats. - Yoshizawa, T (1980)
T-2 toxin was rapidly converted in the 9,000 X g supernatant fraction of rat liver homogenate into HT-2 toxin, T-2 tetraol, and two unknown metabolites designated as TMR-1 and TMR-2. TMR-1 was characterized as 4-deacetylneosolaniol (15-acetoxy-3 alpha, 4 beta, 8 alpha-trihydroxy-12,13-epoxytrichothec-9-ene) by spectroscopic analyses. Since the same metabolites were also obtained from HT-2 toxin used as substrate, it was concluded that T-2 toxin was hydrolyzed preferentially at the C-4 position to give HT-2 toxin, which was then metabolized to T-2 tetraol via 4-deacetylneosolaniol. In addition to HT-2 toxin, 4-deacetylneosolaniol and T-2 tetraol, a trace amount of neosolaniol was transformed from T-2 toxin by rat intestinal strips. In vitro metabolic pathways for T-2 toxin in rats are proposed.